EFFECT OF BABY SPA (SOLUS PER AQUA) ON THE DEVELOPMENT OF GROSS MOTOR ABILITIES OF BABY UMUR 3-6 MONTHS - Flora Niu; Suryati Romauli (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Background: Motor development is a process of Maturity or motion that directly involves the muscles to move and the neural process that a person can move his body. WHO states that 20-40% of babies experience delays, while Indonesia reaches 16%. One way that can be used to meet the needs of motor development is to do a baby spa. Objective: The purpose of this study is to see if the treatment carried out can improve the motor development of infants aged 3-6 months at the Suryati Midwife Independent Practice in Jayapura Regency. Methods: The design of this study uses Pre-Experimental Design with the design Group Pretest-Posttest Design. The population in this study was all babies aged 3-6 months with sampling techniques using Non-Probability Sampling selected by Purposive Sampling consisting of 30 respondents. The variable measured in this study was the motor development of the baby. This study used the Wilcoxon signed rank test (a<0.05). Result: The results showed that the development of babies after a baby spa was higher than before the baby spa. with a value of p=0.002. Thus it can be concluded that the accepted hypothesis means that there is an influence of baby spas on the motor development of the baby. Conclusion: there is an Effect of Baby Spa (Solus Per Aqua) on the Development of Gross Motor Abilities of Babies UNut 3-6 Months Keywords : Baby spa, Motor development